Comparative analysis of commercial partnership in the context of changes in Polish tax law - Janus, Agnieszka A. (Publishing House of Wroclaw University of Economics and Business, 2023)
The aim of the article was to examine the implications of changes in the rules of taxation of the income of limited joint-stock partnerships (LJSP) and limited partnerships (LP) for their dynamics and structure, especially against the background of other commercial partnerships. The hypothesis is that the changes in the rules of taxation of the income of limited joint-stock partnerships and limited partnerships negatively influenced their attractiveness as legal forms of running a business. The research methods used in the article were the analysis of the dynamics of time series, the Fisher-Snedecor test to verify the hypothesis of equality variance and the least squares method. It turns out that the amendment to the tax laws of legal persons/ entities (01.01.2014) by equalising the tax status of the LJSP with the status of legal persons/entities contributed to the increase in the tax burden of those companies, the decline in their numbers in both the commercial partnerships (CP), as well as companies in total in Poland, and in this way the decrease of the structure and dynamics indices. In turn, further changes from 1 January 2021 meant that not only the LJSP ceased to be attractive as a tool to minimise the tax burden for the owners, but also LP. In 2020, the highest decrease in the number of all companies in Poland, amounting to 6.8%, was recorded by LJSP, while in 2021 – LP (7.1%). The results of the Fisher-Snedecor test for the difference in the number of companies calculated year on year confirmed that after 2014 there was a large change in the level of differentiation in the number of limited joint-stock partnerships compared to the previous years. The number of companies decreased rapidly from year to year, which proves the decline in interest in this form of business, and the decline was manifested by a significant increase in data variability, as demonstrated by the Fisher-Snedecor test. The author observed a similar situation for limited partnerships as the change in their number year-on-year was also very differentiated before and after 2014. However, such a conclusion cannot be drawn in relation to general partnerships and partnerships, which indicates that the change in regulations introduced on 1 January 2014 did not affect the trend to create these activities. Additionally, the estimation of regression model parameters for CP group companies showed that the change in the number of LJSP year on year did not change the number of companies of other types.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 213-232
Keywords: tax optimisation; commercial partnership; tax law